Acquired amegakaryocytic thrombocytopenic purpura progressing into aplastic anemia - Novotný, Jan Philipp; Köhler, Birgit; Max, Regina; Egerer, Gerlinde (Prague medical report, 2017)
In this article, we report a case of newly acquired AATP without an associated autoimmune disease, refractory to corticoids, intravenous immunoglobulin (IVIG) and second-generation TPO (thrombopoietin) agonists, which have recently been approved for the treatment of thrombocytopenia. Finally, in accordance with other reports, disease progression into aplastic anemia has occurred.
Gesehen am 20.08.2018